Factors influencing the decision-making behavior of school superintendents - Mendinueto, Cleofe Caspellan
This study investigated the individual and organizational factors in the superintendents decision making behavior in the 56 school divisions in Luzon. The superintendents show common patterns of decision making behavior consisting of a series of acts in this sequence: (1) identifying a problem situation by analyzing data and information; (2) generating ideas and alternative solutions or courses of action through consultation or brainstorming with the staff and personnel; and (3) evaluating or weighing the outcomes of the alternatives before making a decision. The individual variables positively related to decision making behavior (SDMB) are civil status, age, experience, education, special training in educational administration, aggregate family income and occupation of spouse. Of the 7 internal and organizational variables, per pupil cost and class of city/province are positively related to SDMB while influence groups within and outside the organization show positive relationship in certain decision situations and negative relationship in others.